Cyclic and monotonic responses of double shear single dowelled timber connections made of hardwood species: Experimental investigations. (1st February 2017) - Oudjene, M.; Tran, V.-D.; Khelifa, M.
Highlights: Monotonic and cyclic characterization of the structural responses of joints made of hardwood species. Comparison between joints made of hardwood and softwood species. The amount of energy dissipated and the viscous damping ratio were assessed for all wood species. The accuracy of the European Yield Model predictions have been evaluated for hardwood species. Abstract: This paper presents experimental investigations on monotonic and cyclic behaviours of hardwood timber joints. Two sets of connections have been tested: double shear single dowelled timber-to-timber and slotted-in steel plate-to-timber joints. Three wood species have been considered: two hardwood species, namely beech and oak, and spruce for comparison purpose. Both monotonic and cyclic performances of joints have been evaluated and compared to the corresponding values calculated based on the Eurocode 5. The obtained results show clearly the potential interest and performances of hardwood structural joints for high load bearing capacity, as compared to their equivalent softwood joints. The obtained results showed also that the predictions of the European Yield Model regarding the load-carrying capacity penalize the joints made of hardwood species.